Implementasi Model Inkuiri Terbimbing Berbasis Lesson Study dalam Menumbuhkan Kemampuan Argumentasi Komunikasi dan Kognitif Mahasiswa - Uus Toharudin (BIOEDUSAINS: Jurnal Pendidikan Biologi dan Sains, 2020)
This study aims to describe the communication and cognitive argumentation ability of Biology Education students of FKIP Universitas Pasundan Bandung through the application of guided inkuiri model based on Lesson Study on animal ecology concept material. This research is a qualitative descriptive research with biology research subjects as many as 30 people who are attending animal ecology courses in the third semester. Implementation of Class Action Research (RAK) based on lesson study is carried out in 2 cycles, using a guided inkuiri model. Data can be through analysis of the process of activities directly by observers through the filling of student activity sheets for 4 meetings and written tests at the end of the cycle. As a result of the study, in the first phase of writing communication proficiency by 72.3% and the second cycle phase by 85.8%, and for oral in the first cycle phase of 57.8%, and in the second cycle phase by 85.8%. Student cognitive learning outcomes increased significantly by 15.7%, from the first phase of the cycle, with an average score of 60, and the second cycle phase by 72.7%. In conclusion, the ability to argue student communication in the learning process of animal ecology is considered still lacking, but through the application of a guided inkuiri model based on Lesson Study on the concept of animal ecology there is an increase in communication skills both written and oral, as well as the cognitive ability of students to improve. Keywords: Cognitive Learning, Communication Skills, Lesson Study, Inkuiri Model